Genomic Characterization of Mobile Genetic Elements Associated With Carbapenem Resistance of Acinetobacter baumannii From India - Vijayakumar, Saranya; Jacob, Jobin John; Vasudevan, Karthick; Mathur, Purva; Ray, Pallab; Neeravi, Ayyanraj; Baskaran, Ashtawarthani; Kirubananthan, Agilandeeswari; Anandan, Shalini; Biswas, Indranil; Walia, Kamini; Veeraraghavan, Balaji (Frontiers in Microbiology, 2022)
With the excessive genome plasticity, Acinetobacter baumannii can acquire and disseminate antimicrobial resistance genes often associated with mobile genetic elements (MGE). Analyzing the genetic environment of resistance genes often provides valuable information on the origin, emergence, evolution, and spread of resistance. Thus, we characterized the genomic features of some clinical isolates of carbapenem-resistant A. baumannii to understand the role of diverse MGEs and their genetic context responsible for disseminating carbapenem resistance genes. For this, 17 clinical isolates of A. baumannii obtained from multiple hospitals in India between 2018 and 2019 were analyzed. Antimicrobial resistance determinants, the genetic context of resistance genes, and molecular epidemiology were studied using whole-genome sequencing. This study observed an increased prevalence of blaOXA-23 followed by dual carbapenemases, blaOXA-23, and blaNDM. The current study identified three novel Oxford MLST sequence types. The majority of the isolates belonged to the dominant clone, IC2, followed by less prevalent clones such as IC7 and IC8. This study identified variations of AbGRI1 and AbGRI belonging to the IC2 lineage. To the best of our knowledge, this is the first study that provides comprehensive profiling of resistance islands, their related MGEs, acquired antimicrobial resistance genes, and the distribution of clonal lineages of carbapenem-resistant A. baumannii from India.